Analysis of the latest World DanceSport Federation scoring system - Ivanytska, Vitaliya (2015)
In real-life situations it is often very important to set an assessment process fairly and objectively. In order to do that the most appropriate criteria for evaluation should be chosen. Some MCDM methods require additional information about evaluation criteria represented as weights. Recently World DanceSport Federation has adopted a new set of adjudicating rules that uses MCDM processes for evaluation of couples' performance. However, the effectiveness and absence of bias of the new adjudicating system has been actively questioned. Therefore the goal of this thesis is to test the new adjudicating set of rules by introducing possible sensitivity analysis of several selected MCDM methods in regards to weight vector and then by performing it on the data provided from the last world championship.